VD_FINDINFO Jug / 2011 / 271 vom 17. Juni 2011 - VD Tribunal cantonal (2011)
APPRÉCIATION DES PREUVES, CONSTATATION DES FAITS, IN DUBIO PRO REO, PRÉSOMPTION D'INNOCENCE | 6 par. 2 CEDH, 32 al. 1 Cst., 10 CPP (CH)